2013
DOI: 10.1159/000348853
|View full text |Cite
|
Sign up to set email alerts
|

Partial Virological Response to Adefovir Add-On Lamivudine Rescue Therapy in Patients with Lamivudine-Resistant Chronic Hepatitis B

Abstract: Background/Aims: In patientswith lamivudine (LAM)-resistant chronic hepatitis B (CHB)receivingadefovir (ADV) add-on LAM therapy, insufficient viral suppression or the appearance of additional ADV resistance has remained unresolved. This study determined the partial virological response (PVR) criteria to predict a virological response (VR) at week 96 in these patients. Methods: 96 patients with LAM-resistant CHB (ADV add-on LAM therapy >2 years) were analyzed. For predicting VR at week 96, the area under the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Although the area under the receiver operating characteristic curve (0.752) and sensitivity (49.3%) were relatively low, specificity (93.5%) was significantly high. In contrast to a previous study that proposed 500 IU/mL as the optimal cutoff HBV DNA level to predict CVR up to 2‐year rescue therapy, our cutoff (800 IU/mL) might have resulted from the longer follow‐up duration encompassing slow responders to ADV add‐on rescue therapy. Although a previous study with a 5‐year follow‐up suggested that 200 IU/mL at 6 months can be a useful predictor of long‐term virological suppression, these strict criteria might be subject to the risk of unnecessary NUC change.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Although the area under the receiver operating characteristic curve (0.752) and sensitivity (49.3%) were relatively low, specificity (93.5%) was significantly high. In contrast to a previous study that proposed 500 IU/mL as the optimal cutoff HBV DNA level to predict CVR up to 2‐year rescue therapy, our cutoff (800 IU/mL) might have resulted from the longer follow‐up duration encompassing slow responders to ADV add‐on rescue therapy. Although a previous study with a 5‐year follow‐up suggested that 200 IU/mL at 6 months can be a useful predictor of long‐term virological suppression, these strict criteria might be subject to the risk of unnecessary NUC change.…”
Section: Discussionmentioning
confidence: 67%
“…15 Similar to the previous reports, 4.8% of the study population (n = 8) experienced renal impairment. 22,27,28 Based on a recent study suggesting that the optimal time point to predict CVR at 2 years was 1 year rather than 6 months for ADV add-on LAM rescue therapy, 1,2,20 and because our study aimed to assist in determining whether we should change ADV to other NUCs or not, we used HBV DNA level, reduction rate of HBV DNA during the first year, ALT level, and HBeAg positivity after 1 year of rescue therapy instead of at baseline as on-treatment variables to identify independent predictors of CVR during 5-year rescue therapy, together with baseline variables such as age, gender, liver cirrhosis, HBV DNA, and LAM duration. Finally, we found that only HBV DNA level at 1-year rescue therapy significantly predicted CVR during a 5-year period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations